Media Pembelajaran berbasis Website dalam Meningkatkan Pengetahauan Kemaritiman Siswa - Nabilla, Lyzia; Virta Eka Pratiwi, Rantian; Safitri, Rifni Aulia; Firdaus, Salwaa Aulia; Nabilla, Yohanna (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
This research intends to create prototype products that connect inland students to be oriented toward or connected to the sea. Indonesia aspires to become a maritime nation, but those who live upstream or distant from the ocean have not yet made rivers and seas their primary environments. Through a prototype product, this research is anticipated to contribute to the development of the maritime paradigm of the Indonesian people, particularly among students who live far from the ocean. The created goods include maritime materials and subject matter, such as maritime history, culture, resources, and socioeconomics. This study employs a qualitative descriptive approach to research using instruments derived from surveys and analysing datainstruments derived from surveys and analyzing data, this study employs a qualitative descriptive approach to research. The majority of inland pupils have not grasped maritime materials or content, indicating the requirement for a product that can always connect with the sea. On the basis of this issue, a publicly accessible marine website was established to construct a maritime paradigm.